Integrated Management of Mouldy Core and Pink Mould Rot of Apples in Storage under Controlled Atmosphere Conditions - Kumari, Neelam; Sharma, J. N.; Singh, Deepika (International Journal of Economic Plants, 2020)
Effect of pre-cooling, hot water treatment, fumigation, an antagonist (Bacillus subtilis) along with treatment of apple fruits with extract of Emblica officinalis (amla) and coating with neem oil was evaluated for their activity against the fungal growth of Alternaria alternata and Trichothecium roseum, the causal agents of mouldy core and pink mould rot, respectively. Impregnation of fruit trays with botanical formulations was also integrated with other treatments before placing the treated and untreated fruits in controlled atmosphere (CA) storage for four months. The integration of hydro cooling with ice water+CaCl2 (HIWC)+fruit skin coating with neem oil (1%)+placing treated fruits on botanical formulation (BF) impregnated fruit trays (treatment combination T7) prior to CA storage gave highest inhibition of the pathogenic tested fungi with rot incidence of 16.05, 20.46% and fruit rot of 9.05, 11.46%, respectively. The treatment combination T6 in which the antagonist B. subtilis was integrated with pre-cooling and BF-impregnated trays was the next effective treatment with rot incidence of 20.35, 23.07% and fruit rot of 13.34, 17.08%, respectively.